Endosonographic diagnosis of submucosal upper gastrointestinal tumors - Necmettin KARAEREN; Sait BAĞCI; Can UYGURER; Mustafa GÜLŞEN; Kemal DAĞALP; A. ALPER (Turkish Journal of Gastroenterology, 2020)
-